Razvitie navykov psichoreguljacii u sportsmenov v processe sportivnogo soversenstvovanie - Smolenceva, V. N. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The researches carried out by the author had revealed the insufficient level of the development of skills of psychoregulation in athletes of various kinds of sports and qualification It effect negatively on their prestarting condition, counteraction to the influence of stress-factors and the productivity of their competitive activity. This circumstance served as an occasion for the creation of the technology for the development of psychoregulation skills in athletes at different stages of sports perfection.